Sebab-Musabab Istri Tidak Mengajukan Gugatan Atas Harta Bersama (Gono-Gini) Setelah Putusan Perceraian - M. Dju Bire, Chatryen (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Divorced husbands and wives have equal rights to property gono-gini namely assets obtained since they lived together in a legal marriage. Ideally, treasure gono-gini divided between husband and wife who have divorced. In reality, after a divorce, property gono-gini tends to only be controlled by the husband, and on the other hand the wife does not contest her rights to the property gono-gini the. Of course, this is very detrimental to the ex-wife and the children born from the marriage. The research results show that the reason or reasons why wives do not sue their husbands in dividing assets gono-gini as follows: (1) The wife has a job or her own income, (2) The prestige of the wife and her family, (3) The wife is resigned because she does not know how to sue, and (4) The husband's income is small and the husband does not have a job. The government needs to improve the quality and quantity of legal education, including property law gono-gini, both the benefits and the impact if not become the main concern in every marriage. Interference by other parties, including the family, which is too far involved in the household affairs of husband and wife in order to avoid decisions that will actually destroy the existing household. In order for marriage legal counseling to be more effective and efficient, it is necessary to involve religious figures (pastors, ministers, imams and others) in the counseling, including regarding property matters gono-gini. The involvement of religious leaders is believed to be "more effective" in increasing public awareness to better comply with existing social norms. Apart from that, in order to better guarantee the rights and obligations of the parties, especially the rights of the wife, the parties (husband and wife) need to make a marriage agreement which contains, among other things, property issues gono-gini. The marriage agreement in question must be in written form, and not just an oral agreement.